EXTH-34. IN VITRO TUMOR TREATING FIELDS (TTFIELDS) APPLIED PRIOR TO RADIATION ENHANCES THE RESPONSE TO RADIATION IN PATIENT-DERIVED GLIOBLASTOMA CELL LINES. (11th November 2019) - Michelhaugh, Sharon; Mittal, Sandeep
Abstract: Tumor treating fields are FDA-approved for treatment of newly-diagnosed and recurrent glioblastoma. Adding TTFields therapy to standard-of-care extended progression-free survival and overall survival in newly-diagnosed glioblastoma patients. In this study, cell lines generated from newly-diagnosed glioblastoma patients were treated in vitro with TTFields prior to irradiation to determine if the response to radiation would be altered. This study was approved by the WSU Institutional Review Board and written consent obtained from the patients. Single-cell suspensions generated from tumor tissues obtained from newly-diagnosed patients were cultured in DMEM/F12 media with 10% fetal bovine serum and gentamicin. Prior to TTFields initiation, cells were plated on plastic coverslips (5×10 4 cells/coverslip) and incubated overnight. Then, TTFields were applied at 200 kHz with a field intensity of 1.6 V/cm for 3 days. After TTFields application, cells were irradiated with 2, 4, or 6 Gy, or were untreated. After radiation delivery, cells were harvested and replated in a clonogenic assay. From each group, 3 coverslips were each replated in triplicate. After 3 days (3 doubling times), cells were stained with crystal violet and plates were scanned to determine cell counts. Treatment groups were compared to their control group with t-test. For both patient-derived GBM cell lines tested, TTFields prior to radiation decreased the number of crystal violet-stained cells in the clonogenic assay plates. In cell line 15–037, pretreatment with TTFields decreased cell counts by 16, 29, and 56% after 2, 4, or 6 Gy radiation, respectively, compared to the control cells with no TTFields pretreatment (p< 0.05). The response in 14-015S cells was less radiation dose-dependent, with the decrease in cell counts ranging from 33–47% control across the radiation doses (p< 0.05). These data suggest that the use of TTFields therapy prior to radiotherapy may enhance the response to radiotherapy in GBM patients.